2016
DOI: 10.1177/1077546315586495
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation and factors influence analysis on self-excited vibration of tire tread

Abstract: The purpose behind this work is to discuss dynamic stability when self-excited vibration occurs on tire tread. First of all, a suspension-tire-tread model has been built for simulation, and the result shows the existence of self-excited vibration on tire tread under particular conditions. A six-component test of the wheel indicates that self-excited vibration often takes place on tire tread when the vehicle travels straightaway at high speed. Then, through bifurcation analysis of tire tread, we found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In addition, the lateral dynamics of a vehicle driving straight ahead was also studied. 14 The methods are also shown to be useful in the analysis of wheels, tyres and suspension dynamics, with the damping force shown to dramatically affect the behaviour of the suspension 15 and the slip angle and vehicle speed shown to play major roles in the development of vibration. 14 Shimmy behaviour has also been studied, with limit cycles being observed under bisectional road conditions 16 and bistable parameter ranges were found for towed wheels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lateral dynamics of a vehicle driving straight ahead was also studied. 14 The methods are also shown to be useful in the analysis of wheels, tyres and suspension dynamics, with the damping force shown to dramatically affect the behaviour of the suspension 15 and the slip angle and vehicle speed shown to play major roles in the development of vibration. 14 Shimmy behaviour has also been studied, with limit cycles being observed under bisectional road conditions 16 and bistable parameter ranges were found for towed wheels.…”
Section: Introductionmentioning
confidence: 99%
“…In-plane vibration characteristics of the radial tire, such as the vertical vibration (Wu et al., 2017) of the tire, inclusive characteristics (Stojic et al., 2017), and rolling resistance (Miège and Popov, 2005), directly affect the ride comfort of vehicle, acoustic noise, power performance, and fuel economy. Because of the extremely complex structure, material nonlinearity, and geometrical nonlinearity of heavy-loaded radial tires, the analytical characteristics of in-plane testing and modeling belongs to one of the difficult areas of vehicle dynamics research.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the maximum static friction force F m and the sliding friction force F s are determined by the contact status, tire structural parameters and working condition of the tire. The parameter identification method has been discussed in detail in our previous works [4,8,13]. Thus, taking the vehicle speed V , slip angle α, vertical load F z and tire pressure P as variables, the conditions for lateral self-excited vibration are surveyed.…”
Section: Modeling Of Tire Dynamicsmentioning
confidence: 99%
“…Li et al [7] gave speed conditions of the lateral self-excited vibration of tread and found that polygonal wear occurs at a particular vehicle speed that depends on the frequency of lateral self-vibration. Wu et al [8] discussed the dynamic stability of such lateral self-vibration of tread through bifurcation analysis. Zuo et al [9] compared dynamic tread contact con- [1] ditions between the driving wheel and the following wheel and revealed the mechanism behind the tendency for such abnormal wear to appear on the following wheel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation